Paleomagnetic and Geochronologic Results From Late Paleozoic and Mesozoic Rocks of the Central Tibet: Implications for the Paleogeography of the Qiangtang Terrane - Zhao, Xixi; Lippert, Pete; Coe, Rob; Wang, Chengshan; Liu, Zhifei; Yi, Haisheng; Li, Yalin; Deng, Bin; Villa, Igor (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1349 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.177